2014
DOI: 10.11646/zootaxa.3768.3.3
|View full text |Cite
|
Sign up to set email alerts
|

<strong>Faunistic survey of Hydromedusae (Cnidaria, Medusozoa) from the coast of Paraná State, Southern Brazil</strong>

Abstract: This study is the first faunistic inventory of hydromedusae from the inner continental shelf of Paraná State. We describe the composition of hydromedusae species, collected with bottom-trawl and Hensen nets, in campaigns carried out from 1997 to 2006. We analyzed 17,797 specimens from 578 samples, and provide descriptions, photographs, and information about the biology of the 22 species found. All species had previous records from the Brazilian coast; however, this is the first record of Bougainvillia frondosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 65 publications
2
24
1
Order By: Relevance
“…It causes severe skin damage and pain (Kokelj et al 1993). Adults range in size from 6 to 10 cm (Nagata et al 2014) although specimens up to 21 cm were observed in our study area (Mianzan 1986a). This species has a clear seasonal pattern of high-density aggregations during the warmest months (Macchi et al 1995;Mianzan and Ramírez 1996), and were reported in the area from October to April (Mianzan 1986a).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It causes severe skin damage and pain (Kokelj et al 1993). Adults range in size from 6 to 10 cm (Nagata et al 2014) although specimens up to 21 cm were observed in our study area (Mianzan 1986a). This species has a clear seasonal pattern of high-density aggregations during the warmest months (Macchi et al 1995;Mianzan and Ramírez 1996), and were reported in the area from October to April (Mianzan 1986a).…”
Section: Discussionmentioning
confidence: 86%
“…Tentacles with elongate conical bulbs, generally less numerous than radial canals but varying from half to the same number of them; 5-10 statocysts between successive radial canals. Gonads along almost the entire length of the radial canals (Nagata et al 2014) (Fig. 2 C1-3).…”
Section: Aequorea Forskalea Péron and Lesueur 1810mentioning
confidence: 99%
“…and Helgicirrha sp. (Figure 8), could not be identified to species level since the latter is probably an undescribed species, and all the other genera have taxonomic problems (Nagata et al ., 2014a). All the planktonic hydrozoan species found here have already been recorded for the Brazilian coast (Oliveira et al ., 2016), but 19 species are new records for PES and nine for Paraná State (Table 1; Nagata et al ., 2014a).…”
Section: Resultsmentioning
confidence: 99%
“…(Figure 8), could not be identified to species level since the latter is probably an undescribed species, and all the other genera have taxonomic problems (Nagata et al ., 2014a). All the planktonic hydrozoan species found here have already been recorded for the Brazilian coast (Oliveira et al ., 2016), but 19 species are new records for PES and nine for Paraná State (Table 1; Nagata et al ., 2014a). Although these new records fill gaps in their distribution their occurrence was expected, since polyps and/or medusae of them have been found to the south and/or north of the PES (Oliveira et al ., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation